Pengaruh Ukuran Benih Terhadap Perkecambahan dan Pertumbuhan Bibit Tanjung (Mimusops elengi L.) The Effect of Seed Size on Seed Germination and Growth of Tanjung (Mimusops elengi L.) Seedling - N Nurhasybi; Eliya Suita (Jurnal Manajemen Hutan Tropika, 2008)
Tanjung (Mimusops elengi) is a multipurpose tree species, besides the use of its wood for bridge, boat, floor, door, and furnitures, other parts of this tree such as root, leaves and bark, can be used for medicine. This species is one of tree species that potential be developed in planting programme. Tanjung seed has variation in weight and size that need information in how the variation will influence the germination and the seedling growth. The seed has been collected in Padang, West Sumatera. Research was done to examine the influence of seed size to the germination and physical quality of seedling by using the extracted seed. The seeds were divided into three parts in size including large, medium and small. The experiment design was completely ramdomized design. Every unit of the experiment consist of 3 replications that contain 100 seeds each replication for germination and 25 seedlings each replication for the growth of seedling. Sterilized medium for germination and the growth of seedling was mixed of soil and sand (v/v 1:1). The parameters to be observed were germination percentage and speed of germination, and height and diameter of seedling. The results indicated that for collection of tanjung (M. elengi) seeds should be done only at the large and medium size caused by the capability of the seed to grow to be seedling within 3 months in the nursery higher compared to the small size.